G279.0+1.1: a new extended source of high-energy gamma-rays - Araya Arguedas, Miguel (2020)
G279.0+1.1 is a supernova remnant (SNR) with poorly known parameters, first detected as a dim radio source and classified as an evolved system. An analysis of data from the Fermi-Large Area Telescope (LAT) revealing for the first time an extended source of gamma-rays in the region is presented. The diameter of the GeV region found is 2.8 degrees, larger than the latest estimate of the SNR size from radio data. The gamma-ray emission covers most of the known shell and extends further to the north and east of the bulk of the radio emission. The photon spectrum in the 0.5–500 GeV range can be described by a simple power law, with a spectral index of Γ = 1.86 ± 0.03stat ± 0.06sys. In the leptonic scenario, a steep particle spectrum is required and a distance lower than the previously estimated value of 3 kpc is favoured. The possibility that the high-energy emission results from electrons that already escaped the SNR is also investigated. A hadronic scenario for the gamma-rays yields a particle spectral index of ∼2.0 and no significant constraints on the distance. The production of gamma-rays in old SNRs is discussed. More observations of this source are encouraged to probe the true extent of the shell and its age.